Phytochemical Profiling and In Silico Analyses Reveal Druglike Characteristics in the Moss Brachythecium salebrosum (Bryophyta, Brachytheciaceae) - Anshul Dhyani; Kumar Shantanu; Irengbam Rocky Mangangcha; Sanavar Soham; Shruti Kasana; Prem Uniyal (Lilloa)
Bryophytes have long been used as traditional medicine in many Asian countries, particularly China and India. They are known to possess a variety of phytochemicals with known medicinal properties. While bryophytes are broadly recognized for their medicinal potential, the moss Brachythecium salebrosum was selected for this study due to its ecological adaptability and the lack of detailed phytochemical and pharmacological investigations on this species. For the present study, Gas Chromatography-Mass  Spectrometry (GC-MS) coupled with a bioinformatics approach was employed to investigate the  phytochemical constituents and their drug-like affinities in this moss. A total of 55 phytochemical compounds were identified, with four major compounds—phenol, phytol, 2,4-di-tert-butylphenol, and n-hexadecanoic acid, comprising 48.11% of the total compounds. Interestingly, we also reported odd-numbered fatty acids, which are rare in plants. Molecular docking analysis and pharmacokinetic studies of these four compounds revealed robust drug-like properties. The study explored the involvement of certain genes in various metabolic pathways and their associations with different diseases. The findings suggest that B. salebrosum contains a reservoir of medicinally important compounds with drug-like characteristics. This study represents the first comprehensive examination of the phytochemical profiling linked to drug kinetic  studies of this taxon. The presence of new binding sites as reported in this study will further pave the way for drug discovery and development.